First evidence of the Hepatitis E virus in environmental waters in Colombia (2017)
RESUMEN: Hepatitis E virus (HEV) is one of the main causes of acute viral hepatitis of enteric transmission. HEV has been detected in environmental samples in several countries from Europe and Asia, constituting a risk factor for waterborne infection. In Colombia, HEV has been identified in samples obtained from patients as well as from swine, but no environmental studies have been carried out. To determine if HEV is present in environmental waters, samples from the main source of drinking water plant and of wastewater system of eight municipalities and two villages of Antioquia state (North West Colombia), were collected between December 2012 and April 2014. The HEV genome was detected by RT-PCR in 23.3% (7/30) of the samples from the main source of drinking water plants and in 16.7% (5/30) from sewage. Viral concentrates obtained from three positive sewage samples were used to inoculate HepG2 cell cultures that were followed for one month; however, the viral genome was not detected in any cell culture. This study demonstrates the circulation of HEV in both source of drinking water plants and wastewater in Antioquia state, Colombia. The presence of HEV in environmental waters could be a risk for waterborne transmission in this population. The findings of the present study, together with the evidence of HEV circulation in human and swine in Colombia, should be consider by public health authorities for the development of surveillance programs and the inclusion of HEV infection diagnosis in the guidelines of viral hepatitis in the country. This is the first report of HEV in environmental samples in Colombia and the second one in Latin America.